Interaction induced shifts in O-H stretching frequency of water in halide-ion water clusters: a microscopic approach with a bond descriptor - Tanwar, Akhilesh; Bagchi, Biman; Pal, Sourav (Journal of Chemical Physics, 2006)
Based on conceptual density functional theory, two new descriptors, the normalized atom-condensed Fukui functions (NFFs) and bond deformation kernel (BDK), are proposed to describe the O-H stretching frequency shifts in water halide-ion clusters by including local polarizations in the system. NFF, along with BDK, can be successfully used to describe interactions between different atoms, especially in cases where polarizations are quite important. (c) 2006 American Institute of Physics.